Commercial Corporates governance in view of challenges of the Corona pandemic in the Kingdom of Saudi Arabia - Al-Ghamdi, Ola Dhaifallah Ahmed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims at the effectiveness of governance in confronting the Corona pandemic on commercial companies and addressing the legal mechanisms of corporate governance in the Kingdom of Saudi Arabia. The researcher also explains the legal adaptation of the Corona pandemic and the efforts of the Kingdom of Saudi Arabia in confronting the pandemic on the private sector. The study also shows the most important professional and ethical standards to improve performance within commercial companies to reduce corruption. The comparative analytical approach has been applied so that the researcher sheds light on the current situation in the Kingdom of Saudi Arabia to face the effects of the Corona pandemic within the framework of commercial companies governance in addition to comparing some experiences in some other countries. The most important results are that the commercial companies that applied principles of governance are the most capable of facing and overcoming pandemics and crises. The study concludes the most important recommendations, which are the development of a commercial companies governance system so that the articles of the system are binding on all commercial companies in the Kingdom of Saudi Arabia.